Promoting integration of immigrants. Effects of free child care on child enrollment and parental employment - Nina Drange; Kjetil Telle (Statistics Norway, Research Department, 2015)
Proficiency in the language spoken by the majority population may be crucial for the cognitive development of children from immigrant families. High-quality child care is believed to promote such language skills, and it is thus of concern that children from immigrant families are underrepresented in formal child care across OECD countries. How can we increase their participation, and can such participation improve family integration? We study an intervention in some districts of Oslo where children aged four and five were eligible for twenty hours of free childcare weekly. Taking advantage of the intervention being available in some city districts and not in others, we estimate the effect of the intervention on the enrollment of children and on their parents' employment and education, using outcomes measured for the same family before and after the child's age of eligibility. We find that the intervention increased the participation for children from immigrant families by 15 percent. However, we do not find support for effects on parental employment or education. The performance in tests at school entry (age six) for children from immigrant families in city districts with free child care is better than that of similar children in comparison districts. Overall, our results suggest that subsidizing center based child care can improve the cognitive development of children from immigrant families.
Keywords: J13; J15; H52; I28; 330; child care; education; immigrant children; integration; assimilation